Analysis of Livelihood Strategies for Reducing Poverty Among Rural Women's Households: A Case Study of KwaZulu‐Natal, South Africa - Sharaunga, Stanley; Mudhara, Maxwell (Journal of international development, 2021)
This study identifies the livelihood strategies of rural women that are critical for reducing household poverty in Msinga, South Africa. Principal component analysis was used to identify the different livelihood strategies pursued by the women as well as their capital endowments. The probit model was used to assess the livelihood strategies, in addition to capital assets and other socio‐economic factors, which are crucial for poverty reduction among rural households. It was found that certain women's livelihoods, in addition to capital endowments and other socio‐economic factors, are critical to move their households out of poverty. Therefore, humanitarian and development agencies should focus on promoting women's strategies that enhance poverty reduction. © 2020 John Wiley & Sons, Ltd.